Intracortical recording stability in human brain–computer interface users. (15th May 2018) - Downey, John E; Schwed, Nathaniel; Chase, Steven M; Schwartz, Andrew B; Collinger, Jennifer L
Abstract: Objective . Intracortical brain–computer interfaces (BCIs) are being developed to assist people with motor disabilities in communicating and interacting with the world around them. This technology relies on recordings from the primary motor cortex, which may vary from day to day. Approach . Here we quantify, in two long-term BCI subjects, the length of time that action potentials from the same neuron, or group of neurons, can be recorded from the motor cortex. Main results . These action potentials are identified by their extracellular waveforms and may change within a single day, although some of these identified units can be identified consistently for weeks and even months. Features of the extracellular waveforms allowed us to predict whether a specific unit was more or less likely to remain stable over a prolonged period. Significance . A greater understanding of unit stability and instability can aid the development of motor BCIs, where the goal is to maintain a high level of performance despite changes in the recorded population. BCIs should be able to be operated without technician intervention for hours, and hopefully days, to provide the most benefit to the end-users of this technology.